Comparative Embolectomy Outcomes by Age in Patients with Acute Lower Limb Ischemia - Shahzad, Muhammad Aamir; Rehman, Inam Ur; Shabbir, Muhammad Farhan; Malik, Aamir; Makki, Muhammad; Ahmad, Ahsan (Biological and Clinical Sciences Research Journal, 2025)
Acute limb ischemia (ALI) is a vascular emergency associated with high morbidity and mortality. Emergent surgical embolectomy remains the standard of care; however, outcomes may vary with age, comorbidities, and timing of presentation. Limited data exist from South Asian populations evaluating outcomes in elderly versus younger patients. Objective: To compare outcomes of surgical embolectomy between patients aged ≥80 years and those <80 years presenting with acute limb ischemia. Methods: This retrospective study was conducted in the Department of Cardiology, Chaudhary Pervaiz Elahi Institute of Cardiology, Multan, Pakistan, from June 2024 to June 2025. A total of 100 consecutive patients undergoing emergent femoral thromboembolectomy for ALI were included. Patients were stratified into two age-based groups: Group A (≥80 years, n=50) and Group B (<80 years, n=50). All procedures were performed using a standard open femoral approach under 2% prilocaine local anaesthesia. Demographic data, postoperative complications (hematoma, wound infection, acute renal insufficiency/failure), amputation, and mortality were compared between groups. Statistical analysis was performed using the chi-square test, with p<0.05 considered significant. Results: Baseline demographics were comparable across groups. Postoperative complications did not differ significantly between elderly and younger patients. In Group A, 3 (6%) developed hematoma, 3 (6%) wound infection, 11 (22%) required amputation, 9 (18%) had acute renal insufficiency, 7 (14%) acute renal failure, and 9 (18%) died. In Group B, no hematomas occurred; 5 (10%) developed wound infection, 4 (8%) underwent amputation, 4 (8%) had acute renal insufficiency, 2 (4%) developed acute renal failure, and 2 (4%) died. Late presentation was observed in 7 (14%) of Group A and 5 (10%) of Group B. Mortality rates were not significantly different between groups (p=0.31). However, amputation rates were significantly higher in younger patients with late presentation (p=0.001), with compartment syndrome and Buerger’s disease being major contributors. Conclusion: Age alone does not significantly influence outcomes of embolectomy in patients with ALI. Delayed presentation, particularly in younger patients with underlying vascular pathology, is associated with increased risk of limb loss. Early diagnosis and timely intervention remain critical to improving outcomes.